Anaerobic digestion of pre-treated fruits and vegetables wastes : workability of alkaline pre-treatment on fruits and vegetables wastes for anaerobic digestion - Ho, Sze Siew. (2011)
Anaerobic digestion has been widely applied in wastewater sludge to stabilize sewage sludge before disposal since the 1980s and this technology has recently widely gained much attention in its application to municipal solid waste for the recovery of methane gas. For the context of this research paper, Fruits and Vegetables Wastes (FVW) was chosen to be the substrate for anaerobic digestion. In addition alkaline pre-treatment was introduced to break down the complex molecules present in FVW to increase solubilization of organic matter and improve the efficiency of anaerobic digestion.